Current use of complementary and conventional medicine for treatment of pediatric patients with gastrointestinal disorders - Sayre, Casey L.; Yellepeddi, Venkata Kashyap; Job, Kathleen M.; Krepkova, Lubov V.; Sherwin, Catherine M. T.; Enioutina, Elena Y. (Frontiers in Pharmacology, 2023)
Infants, children, and adolescents are at risk of experiencing a multitude of gastrointestinal disorders (GID). These disorders can adversely affect the quality of life or be life-threatening. Various interventions that span the conventional and complementary therapeutic categories have been developed. Nowadays, parents increasingly seek complementary options for their children to use concurrently with conventional therapies. Due to the high prevalence and morbidity of diarrhea, constipation, and irritable bowel syndrome (IBS) in children, in this review, we decided to focus on the current state of the evidence for conventional and complementary therapies used for the treatment of these diseases in children. Diarrhea treatment focuses on the identification of the cause and fluid management. Oral rehydration with supplementation of deficient micronutrients, especially zinc, is well established and recommended. Some probiotic strains have shown promise in reducing the duration of diarrhea. For the management of constipation, available clinical trials are insufficient for conclusive recommendations of dietary modifications, including increased use of fruit juice, fiber, and fluid. However, the role of laxatives as conventional treatment is becoming more established. Polyethylene glycol is the most studied, with lactulose, milk of magnesia, mineral oil, bisacodyl, and senna presenting as viable alternatives. Conventional treatments of the abdominal pain associated with IBS are poorly studied in children. Available studies investigating the effectiveness of antidepressants on abdominal pain in children with IBS were inconclusive. At the same time, probiotics and peppermint oil have a fair record of benefits and safety. The overall body of evidence indicates that a careful balance of conventional and complementary treatment strategies may be required to manage gastrointestinal conditions in children.